In uncharted territory “together each achieves more”: a United Nations interagency collaboration for continuity of maternal and newborn health services during the coronavirus pandemic in the Eastern and Southern Africa region - Bergh, Anne-Marie; Gohar, Fatima; Kidula, Nancy A.; Abdullah, Muna (Frontiers in Health Services, 2023)
The frangible collaboration between three United Nations agencies (UNICEF, UNFPA and WHO) in the Eastern and Southern Africa Region was strengthened by the outbreak of the coronavirus pandemic. The aim was to combine existing resources and expertise to support countries to respond to the pandemic more effectively and efficiently regarding the provision of maternal and newborn health services. Three kinds of activities were conducted: 15 webinars on a variety of topics and issues impacted by the pandemic; virtual training on maternal and perinatal death surveillance and response as well as on quality improvement; and the development of online e-learning modules for continuous professional development. Key dimensions of the collaboration included: a common vision; commitment to the process; dialogue; building relationships and trust; communication and information sharing; sharing of technical and financial resources and expertise; mobilization of additional resources; celebration of intermediate outcomes; facilitative leadership; and institutional design. Start-up lessons revolved around shared risk taking, while retaining agency autonomy. Collaboration lessons included forming a 'united front', harnessing technology to accelerate results, and mitigating adverse structural and contextual factors. There are widespread perceptions that collaborative initiatives tend to yield minimum results in terms of increased efficiency or effectiveness. This particular collaborative effort demonstrated elements of feasibility, value addition, synergy, cost effectiveness and demonstrable results where UN agencies delivered as one. The emergency in healthcare as a ripple effect of the coronavirus pandemic has caused a rethink of collaboration models and levels of engagement.